Sleep problems, behavioural problems and respiratory health in children born extremely preterm: a parental questionnaire study - Bjørn Bjorvatn; Thomas Halvorsen; Mari Hysing; Trond Markestad; Kristine Marie Stangenes; Irene Bircow Elgen (BMJ Publishing Group, 2019)
Objective To explore whether children born extremely preterm (EPT) with different types of sleep problems had more behavioural and respiratory health problems than EPT children without sleep problems.Design Prospective, nationwide, questionnaire-based study. At 11 years of age, parents reported on four current sleep problems: difficulty falling asleep or frequent awakenings, snoring, daytime sleepiness and not recommended sleep duration (<9 hours). Behavioural problems were assessed by parents and teachers with the Strengths and Difficulties Questionnaire (SDQ). Parents assessed respiratory symptoms with the International Study of Asthma and Allergies in Childhood questionnaire and described use of asthma medication.Setting Norway.Patients EPT children.Main outcome measures Specified sleep problems, behavioural problems and respiratory health.Results Data were obtained from 216 of 372 (58 %) of eligible children. All four specified sleep problems were associated with significantly higher parent-reported SDQ total-score (OR 1.1 for all), and except for not recommended sleep duration, also with higher teacher-reported SDQ total-score (OR 1.1 for all). Daytime sleepiness was strongly associated with wheezing last 12 months (OR 3.4), disturbed sleep due to wheezing (OR 3.9), wheeze during or after exercise (OR 2.9), use of inhaled corticosteroids or oral leukotriene modifiers (OR 3.4) and use of bronchodilators (OR 3.9). Snoring was associated with wheezing during or after exercise (OR 2.8) and current asthma (OR 4.2).Conclusion EPT children with different types of sleep problems had more behavioural and respiratory health problems than EPT children without sleep problems.